Ramsay Hunt syndrome. Issue 2 (1st August 2001) - Sweeney, C J; Gilden, D H
Abstract : The strict definition of the Ramsay Hunt syndrome is peripheral facial nerve palsy accompanied by an erythematous vesicular rash on the ear (zoster oticus) or in the mouth. J Ramsay Hunt, who described various clinical presentations of facial paralysis and rash, also recognised other frequent symptoms and signs such as tinnitus, hearing loss, nausea, vomiting, vertigo, and nystagmus. He explained these eighth nerve features by the close proximity of the geniculate ganglion to the vestibulocochlear nerve within the bony facial canal. Hunt's analysis of clinical variations of the syndrome now bearing his name led to his recognition of the general somatic sensory function of the facial nerve and his defining of the geniculate zone of the ear. It is now known that varicella zoster virus (VZV) causes Ramsay Hunt syndrome.  Compared with Bell's palsy (facial paralysis without rash), patients with Ramsay Hunt syndrome often have more severe paralysis at onset and are less likely to recover completely. Studies suggest that treatment with prednisone and acyclovir may improve outcome, although a prospective randomised treatment trial remains to be undertaken. In the only prospective study of patients with Ramsay Hunt syndrome, 14% developed vesicles after the onset of facial weakness. Thus, Ramsay Hunt syndrome may initially be indistinguishable from Bell's palsy. Further, Bell's palsy is significantly associated with herpes simplex virus (HSV) infection. In the light of the known safety and effectiveness of antiviral drugs against VZV or HSV, consideration should be given to early treatment of all patients with Ramsay Hunt syndrome or Bell's palsy with a 7–10 day course of famciclovir (500 mg, three times daily) or acyclovir (800 mg, five times daily), as well as oral prednisone (60 mg daily for 3–5 days).  Finally, some patients develop peripheral facial paralysis without ear or mouth rash, associated with either a fourfold rise in antibody to VZV or the presence of VZV DNA in auricular skin, blood mononuclear cells, middle ear fluid, or saliva. This indicates that a proportion of patients with "Bell's palsy" have Ramsay Hunt syndrome zoster sine herpete. Treatment of these patients with acyclovir and prednisone within 7 days of onset has been shown to improve the outcome of recovery from facial palsy.